Prevalence and Correlates of Dental Fear, Pain, and Cariesin Libyan Children and Adolescents: A Cross-Sectional Studyin Three Northeastern Citie - BENTAHER, HIATHAM; AYOUB, GIUMA (Sharwes Scientific Journal, 2025)
Dental fear and anxiety (DFA) remain significant barriers to timely and effective oral healthcare forchildren and adolescents, frequently leading to avoidance behaviours and increased risk of untreateddental conditions. While global evidence highlights the prevalence and consequences of DFA,populations in North Africa particularly in Libya are underrepresented in epidemiological data. Thiscross-sectional study examined the prevalence of DFA, dental pain, and caries, and their associationswith sociodemographic, behavioural, and clinical variables among 1,800 children and adolescents aged6 to 17 years attending public clinics in Al Bayda, Derna, and Tobruk. Data were collected through fivestructured tools: the Sociodemographic and Behavioural Profile Scale (SDBPS), Dental Pain andDiscomfort Scale (DPDS), Children’s Fear Survey Schedule–Dental Subscale (CFSS-DS), SelfReported Caries History Scale (SRCHS), and Clinical Examination Record (CER). Analysis revealedthat younger age and female gender were significantly associated with higher DFA scores (p < 0.001).Recent dental pain strongly predicted elevated anxiety levels (β = 0.34, p < 0.001), while irregularbrushing and lack of prior dental visits correlated with both higher DFA and greater caries prevalence(OR = 2.32, p < 0.001). Lower maternal employment was also associated with increased risk of cariesand DFA (OR = 1.87, p = 0.004). The findings suggest that emotional distress and clinical burden arejointly influenced by behavioural routines and structural disadvantage. These results highlight the needfor integrated, age-appropriate, and socially responsive oral health strategies that simultaneously addresspsychological barriers and promote equitable access to preventive care for children in underservedLibyan regions.